1970
DOI: 10.5424/sjar/20110904-515-10
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition of a new Lupinus species found in Spain, Lupinus mariae-josephi H. Pascual (Fabaceae)

Abstract: A new lupin from Valencia (Spain) has been described recently. The new species Lupinus mariae-josephi H. Pascual (Fabaceae) differs from any other Mediterranean and North American taxon in banner position, flower colour and inflorescence structure. This species was found in a calcareous area, and when it was grown in experimental fields it has always performed better in alkaline soils. This work attempts to establish the content of protein, oil and nutritionally active factors (alkaloids, α-galactosides and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 23 publications
2
7
0
2
Order By: Relevance
“…found in L. barkeri. In the studies of Muzquiz et al [28], fat content in the seeds of L. mariae-josephi was similar to L. luteus and L. hispanicus, and at the same time lower than in the seeds of L. mutabilis and L. albus. Garcia-Lopez et al [29] determined that fat content in L. mexicanus amounted to, on average, 5.7%, while in L. montanus it was two-fold higher.…”
Section: Resultsmentioning
confidence: 81%
“…found in L. barkeri. In the studies of Muzquiz et al [28], fat content in the seeds of L. mariae-josephi was similar to L. luteus and L. hispanicus, and at the same time lower than in the seeds of L. mutabilis and L. albus. Garcia-Lopez et al [29] determined that fat content in L. mexicanus amounted to, on average, 5.7%, while in L. montanus it was two-fold higher.…”
Section: Resultsmentioning
confidence: 81%
“…The sucrose content of lupin ranged between 1.5 to 3.5 , why stachyose ranged between 6.0 and 7.5 . Raffinose contents which was found to be 33.2 g/kg was significantly higher than verbascose 8.49 g/kg in lupin seeds 36 . According to Muzquiz et al 11 , lupin L. mariae-josephi seeds contain 79.1 g/kg oligosaccharides.…”
Section: Fatty Acid Composition Of Millet Sorghum and Lupin Seedsmentioning
confidence: 69%
“…Overall, protein content in researched lupines was greater than those found in other Mexico wild species as L. refl exus (37.31g/100 g ), L. splendens (37.2), L. campestris (39.7) and L. barkeri (37.07 g/100 g ) [2,14,17] and from Spain, such as L. gredensis (23.8g/100 g ), L. mariaejosephi (32.9) and L. luteus (33.6g/100 g ) [19,20] and similar to the domesticated varieties of L. albus, L. luteus and L. angustifolius (30 to 40 g/100 g ) [21]. All of the seeds had a slight reduction in protein due to the thermal treatment but not signifi cant, with exception of L. rotundifl orus with a signifi cant reduction (p< 0.05) of 41.96 to 37.52 g/100 g. These results do not coincide with those reported by Jiménez et al, [2] whom observed an increase of this nutrient in Lupinus campestris seeds of 39.7g/100 g to 49.7g/100 g after being submitted to a six hour thermal treatment.…”
Section: Resultsmentioning
confidence: 99%